Population Pharmacokinetics of Colistin Sulfate in Critically Ill Patients: Exposure and Clinical Efficacy - Yu, Xu-ben; Zhang, Xiao-Shan; Wang, Ye-Xuan; Wang, Yu-Zhen; Zhou, Hong-Min; Xu, Fang-Min; Yu, Jun-Hui; Zhang, Li-Wen; Dai, Ying; Zhou, Zi-Ye; Zhang, Chun-Hong; Lin, Guan-Yang; et al. (Frontiers in Pharmacology, 2022)
Background Presently, colistin is commercially available in two different forms, namely colistin sulfate and its sulphomethylated derivative, colistimethate sodium (CMS). However, in the currently reported studies, most of the clinical studies on colistin for parenteral use is refer to CMS. Data on the pharmacokinetics (PK), clinical efficacy, and side effects of colistin sulfate in clinical use have not been reported. Methods This retrospective study was performed in carbapenem-resistant organisms (CRO)- infected patients treated with colistin sulfate for more than 72 hours. The population pharmacokinetic model was developed using the NONMEM program. The clinical outcomes including clinical treatment efficacy, microbiological efficacy, and nephrotoxicity were assessed. Monte Carlo simulation was utilized to calculate the probability of target attainment (PTA) in patients with normal or decreased renal function. Results A total of 42 patients were enrolled. 25 (59.52%) patients were considered clinical treatment success, 29 (69.06%) patients had successful bacteria elimination at the end of treatment. Remarkably, no patient developed colistin sulfate-related nephrotoxicity. A total of 112 colistin concentrations with a range of 0.28 to 6.20 mg/L were included for PK modeling. The PK characteristic of colistin was well illustrated by a 1-compartment model with linear elimination, and creatinine clearance (CrCL) was identified as a covariate on the clearance of colistin sulfate that significantly explained inter-individual variability. Monte Carlo simulations showed that the recommended dose regimens by the label sheet of colistin sulfate that daily dose of 1 – 1.5 million IU/day, given in 2-3 doses could attain PTA > 90% for MICs ≤ 0.5 μg/mL, but it was risking of subtherapeutic exposure for MIC ≥ 1 μg/mL in renal healthy patients at the daily dose of 1 million IU/day. Conclusion Renal function significantly affects the clearance of colistin sulfate. A dose of 750,000 U every 12 h was recommended for pathogens with MIC≤ 1 μg/mL. The dosage recommended by the label inserts had a risk of subtherapeutic exposure for pathogens with MIC≥2 μg/mL. Despite patients with acute renal insufficiency have higher exposure, dose reduction was not recommended.